2007
DOI: 10.1037/0012-1649.43.4.838
|View full text |Cite
|
Sign up to set email alerts
|

Young children's social information processing: Family antecedents and behavioral correlates.

Abstract: Little research has examined whether social information processing (SIP) measures from early childhood predict externalizing problems beyond the shared association with familial risk markers. In the present study, family antecedents and first-grade externalizing behaviors were studied in relation to preschool and 1st-grade SIP using data from the U.S. National Institute for Child Health and Human Development Study of Early Child Care (N ϭ 1,364). A subgroup of low-risk children reported only benign attribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
98
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(113 citation statements)
references
References 65 publications
12
98
2
1
Order By: Relevance
“…What seems to be particularly characteristic of reactively aggressive children is their tendency to suspect hostile intentions in others when a social situation leads to a negative outcome for themselves, even when the other person's intention is ambiguous (Crick and Dodge 1996;Dodge and Coie 1987;Schwartz et al 1998). Some scholars have suggested that this hostile attribution bias may be due to an underlying lack of theory of mind skills (Katsurada and Sugawara 1998;Orobio de Castro et al 2002;Runions and Keating 2007). In support of this notion, our findings showed that low theory of mind skills are indeed related to higher levels of reactive aggression.…”
supporting
confidence: 86%
See 4 more Smart Citations
“…What seems to be particularly characteristic of reactively aggressive children is their tendency to suspect hostile intentions in others when a social situation leads to a negative outcome for themselves, even when the other person's intention is ambiguous (Crick and Dodge 1996;Dodge and Coie 1987;Schwartz et al 1998). Some scholars have suggested that this hostile attribution bias may be due to an underlying lack of theory of mind skills (Katsurada and Sugawara 1998;Orobio de Castro et al 2002;Runions and Keating 2007). In support of this notion, our findings showed that low theory of mind skills are indeed related to higher levels of reactive aggression.…”
supporting
confidence: 86%
“…Indeed, evidence suggests that the relation between cognitive skills and social behavior may not be a linear one and is often moderated by social context (Crick and Dodge 1994;Dodge et al 2003;Gibb and Coles 2005). Young children who have difficulties inferring another person's perspective may thus rely on their own perception of reality that is based on previous experiences to interpret the situation (Runions and Keating 2007). If these previous experiences are negative, the child may interpret the situation as threatening and react aggressively.…”
Section: Peer Victimization Experiences As a Potential Moderator Of Tmentioning
confidence: 99%
See 3 more Smart Citations